APLIKASI INFORMASI DIGITAL FAKULTAS ILMU KOMPUTER UNIVERSITAS MUSLIM INDONESIA - Tanti, Tri Gustanti (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2024)
The selection of the appropriate information media is very important in supporting the success of delivering information to those concerned, including the Faculty of Computer Science, University of Muslim Indonesia.Furthemore, this research is made with the title